Empty nest syndrome: A concept analysis - Maryam Ahmadi Khatir; Mahnaz Modanloo; Ali Dadgari; Leila Teymouri Yeganeh; Homeira Khoddam (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Empty nest syndrome (ENS) is parents' experience to their children leaving home. Considering the lack of a clear definition of this concept and its context-based nature, this study aimed to define the ENS concept. MATERIALS AND METHODS: A three-phase concept analysis using a hybrid model was used. In the theoretical (first) phase, a literature review was conducted using Scopus, WOS, PubMed, ProQuest, Irandoc, Research.idml, Magiran, and SID, with the search terms "empty nest syndrome," "aged," and "middle-aged," and their synonyms, with no time and language restrictions until the end of 2021. After the screening, 29 relevant articles entered the study. According to the findings of the first phase, the fieldwork (second) phase was directed using the qualitative content analysis approach, and semi-structured interviews were conducted with nine elderly and middle-aged individuals with an open-ended question. Results from both were included in the final (third) phase. RESULTS: The theoretical phase created an operational definition to guide the fieldwork phase. The fieldwork phase resulted in the emergence of six themes. The final analysis phase formulated a comprehensive definition of this concept: "ENS is a subjective phenomenon that occurs as a result of parents' reaction to their children leaving home." This transition from crisis to self-regaining includes the stages of mourning or resistance reaction, feelings of loss or passive behaviors, sublimation or impulsive behaviors, adaptation, and relief. It initiates with the last child's departure and continues until two years. CONCLUSION: Exploration of the concept of ENS can be the basis for designing a model or theoretical framework, devising measurement instruments for the concept and its consequences, and developing programs to increase the healthcare team's awareness to identify the problem and conduct appropriate preventive or therapeutic measures.